Le VIH au Chili. Usages politiques de la vérité technique - Eduardo Carrasco-Rahal (Cahiers des Amériques Latines, 2021)
The technical truth is defined here as a scientifically determined truth, validated by an epistemic community prior to ratification by political authorities. To illustrate the political uses of technical truth we have chosen the Chilean example of two lines of argument in the area of HIV prevention, both using scientific arguments. The first, which is secular, is inspired by international medical organizations and advocates the use of condoms, while the second, of Catholic inspiration, promotes abstinence and fidelity. These two technical truths clash in a public controversy, the aim of which is not to establish scientific supremacy but to exert influence on public opinion and decision makers. We will see, after an analysis that is as much of scientific as of epistemological interest, that the hesitations of the political world around these two truths resulted in a dramatic increase of new cases of AIDS in Chile.